Genome-wide identification and analysis of autophagy-related (ATG) genes in Lycium ruthenicum Murray reveals their crucial roles in salt stress tolerance - Shi, Yi (Plant science : an international journal of experimental plant biology, 2024)
Copyright © 2024 Elsevier B.V. All rights reserved.